Exploring the Motivations Behind Borrowing Company Names in Construction Service Auctions: A Case Study in Jambi Province - Afianto, Vicky; Wardhana, Arief Wisnu; Mahfuz, Abdul Latif (Jurnal Ilmu Hukum Kyadiren, 2025)
The government’s procurement of goods and services is a critical component in supporting the implementation of development initiatives in Indonesia, particularly within government agencies. This study examines the factors that drive the practice of borrowing company names in construction consultant service auctions in Jambi Province. Using a normative legal method, the study seeks to identify the motivations behind the involvement of individuals or business entities in such practices. The findings reveal several contributing factors, including the lack of or inconsistency in obtaining a Construction Service Business Entity Certificate (SBU), limited capital, the desire to leverage a well-known name, efforts to avoid the legal process, and ignorance or negligence of legal requirements. Additionally, the misuse of registered names and reliance on established company reputations emerge as significant motivations.